Perubahan Struktur Bahasa dalam Komunikasi Digital di Media Sosial - Yusuf Idin Adhar; Muhammad Wadhani; Muh. Addarunnafis; Hidayatunnisa’i Hidayatunnisa’i (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The development of information technology and social media has given rise to new forms of communication that have impacted changes in language structure in society. This study aims to describe the forms of changes in language structure in digital communication on social media, particularly on the Facebook and Instagram platforms, and to explain the social factors behind them. The method used is a descriptive qualitative approach, with documentation and observation techniques on posts by users aged 15–45 years. The results of the study indicate that changes in language structure on social media include several main forms: (1) ellipsis, which is the removal of sentence elements that can be understood from the context; (2) shortening and abbreviation of words for communication efficiency; (3) the use of emoticons and symbols as substitutes for nonverbal expressions; (4) code mixing between Indonesian and English as a marker of social identity and globalization; and (5) phonetic modification and spelling creativity as a form of personal expression and communication style typical of the digital generation. These changes are not considered as language deviations, but rather forms of linguistic adaptation to the fast, concise, and expressive nature of communication in the digital space. This study confirms that social media is a dynamic space for language evolution, where creativity and efficiency are the main principles in communication.